Trade Marks and Brands: An Interdisciplinary Critique - Bently, Lionel (Cambridge University Press, 2013)
Recent developments in trade mark law have called into question a variety of basic features, as well as bolder extensions, of legal protection. Other disciplines can help us think about fundamental issues such as: What is a trade mark? What does it do? What should be the scope of its protection? This volume assembles essays examining trade marks and brands from a multiplicity of fields: from business history, marketing, linguistics, legal history, philosophy, sociology and geography. Each part pairs lawyers’ and non-lawyers’ perspectives, so that each commentator addresses and critiques his or her counterpart’s analysis. The perspectives of non-legal fields are intended to enrich legal academics’ and practitioners’ reflections about trade marks, and to expose lawyers, judges and policy-makers to ideas, concepts and methods that could prove to be of particular importance in the development of positive law.